A coupled three-phase FE-model for dewatering of soils by means of compressed air - Oettl, Gerhard; Stark, Rudolf F.; Hofstetter, Guenter (Computer Assisted Methods in Engineering and Science, 2003)
A coupled three-phase soil model, consisting of a deformable soil skeleton and the fluid phases water and compressed air, applicable for tunnelling below the ground-water table by means of compressed air, is presented. In this model interactions of the flow of the fluids in the soil with the deformations of the soil skeleton are taken into account in a physically consistent manner. The theoretical background and the implementation of the model into a finite element code are briefly addressed. Several applications dealing with the numerical simulation of laboratory tests and a full-scale in-situ experiment are discussed. These experiments focus on the flow of (compressed) air in dry as well as semi-saturated soil.